KAJIAN STATUS KUALITAS PERAIRAN JANGARI CIRATA DAN KELAYAKANNYA UNTUK DAERAH WISATA AIR - Soetrisno, Yudhi (Jurnal Teknologi Lingkungan, 2005)
Jangari is an area in Cirata reservoir that was developed for tourism area. Lately, in this area have been developed many cages for fish culture that produce organic waste in huge number. This research was conducted to know the status and dynamics of water quality in Jangari that receive organic waste in huge number.The research revealed that Jangari water body could be cited as an eutrophic water body. This conclusion was due to (i)-the concentrations of phosphorus was always higher than 0,016 mg•l-1P and nitrogen total was always higher than 0,711 mg•l-1N; (ii)-the density of fitoplankton in 25 cm depth was between 36.590•103 and 40.710•103 ind•l—1; whereas in 150 cm depth was between 29.620•103 and 36.370•103 ind•l—1. This phytoplankton community was dominated byCyanophyta (70,9%-78,2%), especially. Microcystis sp and Oscillatoria sp. (iii)-the vanishing point of secchi disc was always smaller than 71 cm. During the research zooplankton was dominated by copepoda, cladocera and rotifera with density fluctuate between 34-394 ind•l—1. The eutrophic status for Jangari, will threaten the sustainable potency for tourism area; and therefore it was suggested to built one management for Cirata reservoir which could be hoped to plan, do and evaluate the development of Cirataappropriate to the potencies and carryng capasity of reservoir.